Structure and biogeochemical process of microaggregates in a water source area of China’s South-to-North Water Diversion Project according to different land use types - Li, Chunjie; Guo, Shili; Shang, Songhao; Qi, Pengcheng; Li, Bailian (Frontiers in Environmental Science, 2023)
Soil biogeochemical processes have the potential to influence water quality in the source area of China's Middle Route of the South-to-North Water Diversion Project. In order to explore the differences in biochemical processes and their mechanisms at the microaggregate scale for different land use types, four typical land-use types—forest, shrubland, terraces and cultivated land—were compared. The microaggregates were characterised using scanning electron microscopy (SEM), SEM-EDS plane-scan analysis, X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF) and Fourier transform infrared (FTIR). The results indicated that microaggregates from forest and shrubland had a flocculent spatial structure, those from terraces had a non-directional plate-like spatial structure, and those from cultivated land had a laminar spatial structure. Additionally, elements such as Mg, Al and Fe were found to be enriched in clay particles when combined with microaggregates. Furthermore, the mineral composition of clay was seen to vary significantly between different land-use practices; illite, chlorite, anorthite, albite and quartz were observed to be present in higher proportions in terraces and cultivated land than in forest and shrubland. Moreover, the contents of transitional elements such as Ti, Fe, Zn, Y and Zr increased with each successive land-use practice. Soil organic matter (SOM) was observed to decline in the order of forest > shrubland > terraces > cultivated land; the relatively low SOM content in cultivated land could potentially be attributed to over-tillage. Degradation of aggregate structure appears to be the main mechanism of organic matter loss due to long-term tillage. The results of this study may be important for understanding soil erosion and chemical transport dynamics.